Leksikografisk radikalisme? 10 forslag til den bilingvale ordbog - Farø, Ken (Nordiske Studier i Leksikografi, 2006)
Lexicographic Radicalism? 10 Proposals for the Bilingual Dictionary. A tendency in bilingual dictionaries towards what could be called automatism rooted in traditionalism is investigated and a number of possible solutions are proposed under the heading “lexicographic radicalism”. This notion by no means indicates a new theoretical challenge to lexicography. Instead, it focuses on typical problems in bilingual dictionaries which – at least within a functional concept – may not be as self-evident as they may seem. The problems discussed could be divided into those of inclusion: variance, paradigm copying, and transparency; those of omission: fictionyms, frequency information, error forms, pragmatics, and illustrations; and those of treatment: culture specific lexemes and idioms. The list presented is neither new in every detail nor complete but should be revised as old problems are solved and new ones arise. “Lexicographic radicalism” could be seen as a complex of non-trivial critique towards wide-spread traditions in bilingual lexicography.